Active search for antecedents in cataphoric pronoun resolution - Pablos, Leticia; Doetjes, Jenny; Ruijgrok, Bobby; Cheng, Lisa L.-S. (Frontiers in Psychology, 2015)
Cataphoric dependencies where a pronoun precedes its antecedent appear to call on different mechanisms in language comprehension from forward dependencies where the antecedent precedes the pronoun. Previous research has shown that the resolution of cataphoric dependencies involves predictive processes such as the Active Search Mechanism, which hypothesizes the automatic search for an antecedent immediately after encountering a cataphoric pronoun. The current study employs gender mismatch to investigate whether the active search for an antecedent of a cataphoric pronoun is restricted only to grammatically licit positions. We present results from an event-related potential experiment on the reading comprehension of cataphoric dependencies in Dutch. Results show that gender mismatch gives rise to an anterior negativity at grammatically licit antecedent positions only. We hypothesize that this negativity reflects the prediction failure for an antecedent after encountering a pronoun, rather than a gender mismatch. We discuss the timing, topography and functionality of this negativity with respect to previous studies and how this relates to the ERPs elicited in the processing of structural constraints on pronoun resolution.